Analysis of the light regulatory mechanism in carotenoid production in Rhodosporidium toruloides NBRC 10032. Issue 8 (14th June 2021) - Pham, Khanh Dung; Hakozaki, Yuuki; Takamizawa, Takeru; Yamazaki, Atsushi; Yamazaki, Harutake; Mori, Kazuki; Aburatani, Sachiyo; Tashiro, Kosuke; Kuhara, Satoru; Takaku, Hiroaki; Shida, Yosuke; Ogasawara, Wataru
ABSTRACT: Light stimulates carotenoid production in an oleaginous yeast Rhodosporidium toruloides NBRC 10032 by promoting carotenoid biosynthesis genes. These genes undergo two-step transcriptional activation. The potential light regulator, Cryptochrome DASH (CRY1), has been suggested to contribute to this mechanism. In this study, based on KU70 (a component of nonhomologous end joining (NHEJ)) disrupting background, CRY1 disruptant was constructed to clarify CRY1 function. From analysis of CRY1 disruptant, it was suggested that CRY1 has the activation role of the carotenogenic gene expression. To obtain further insights into the light response, mutants varying carotenoid production were generated. Through analysis of mutants, the existence of the control two-step gene activation was proposed. In addition, our data analysis showed the strong possibility that R. toruloides NBRC 10032 is a homo-diploid strain. Graphical Abstract: